Competitiveness Analysis and Factors Affecting Trade of Main Commodities between Indonesia and Turkey - Fauziyah Adzimatinur (Universitas Kuningan, 2018)
This study aims to analyze the competitiveness, trade integration, trade complementarity, and factors affecting the export and import of main commodities between Indonesia and Turkey. Data used in this study is time series data in 1996-2018 and the methods used are Revealed Comparative Advantage (RCA), Intra-Industry Trade (IIT), Trade Complementarity Index (TCI), and Ordinary Least Square (OLS). Results of RCA showed Indonesia's main export commodities to Turkey are woven fabrics, stearic acid, palm oil and natural rubber. While IIT showed that there is only one way trade from Indonesia. Import commodities from Turkey are carpets, borax, wheat flour, and tobacco. TCI showed low complementarity between Indonesia’s export and Turkey’s import. GDP per capita has positive impact on exports and imports. The exchange rate has positive impact on exports and negative on imports. Price and tariff rate have negative impact on both exports and imports. Dummy Non-tariff barrier has negative impact on exports while in import side, it only affects the wheat flour negatively. The Government of Indonesia should pursue a strategy in trade cooperation as efforts to reduce trade barriers such as tariffs and non-tariffs for some commodities that have competitiveness in the Turkish market.